The impact of knowledge sharing behaviour and social intelligence of university academics on their performance: The mediating role of competencies - Kularajasingam, Janitha; Subramaniam, Anusuiya; Singh, Devinder Kaur Sarjit; Sambasivan, Murali (Taylor and Francis, 2022)
Generally, university academics’ knowledge sharing behavior and social intelligence are said to be significant in improving their performance through their grasp of competencies Nevertheless, the association has yet to be thoroughly researched. Thus, this study applied the proposed mediation model among university academics in the Business School of seven Malaysian private universities. The salient findings of this research are that the competencies mediate the association among (1) knowledge sharing behavior and innovative teaching and (2) social intelligence and innovative teaching. Apart from that, it was observed that knowledge sharing behavior impacted innovative teaching and supervision, while social intelligence impacted innovative teaching, research and publication and supervision. Implications were discussed.